Analysis on the Machining Twisting mechanism of Tooth Surface with Axial Modification of Helical Gear and Its Influence on Meshing Performance - Shihao Gao; Long Yang; Siyu Chen; Jinyuan Tang (Jixie chuandong)
The formation mechanism of tooth surface twist in helical gear generating machining （worm grinding and hobbing） and the measure to reduce the tooth surface twist are mainly studied. Based on the diagonal worm grinding or hobbing machining method， the tooth surface equation of helical gears with axial modification is constructed. The standard helical gear tooth surface and the helical gear machining tooth surface with axial modification are compared to obtain the correlation law between the speed ratio of axial feed and diagonal feed of the generating tool （worm or hob） and tooth surface twist. Based on the derived tooth surface equation of the helical gear with axial modification， Matlab and CATIA combined modeling technology is used to establish a three-dimensional geometric model of the helical gear pair with axial modification. The simulation analysis of the meshing performance of the gear pairs with different levels of tooth surface twist shows the influence of tooth surface twist on the meshing performance. The research shows that， the larger the helix angle of helical gear with axial modification is， the more serious the tooth surface twist is. Modification amount does not affect the twist of the tooth surface. The ratio of the axial feed and diagonal feed of the tool has the best match with the tooth surface twist. Improved tooth surface twist can effectively reduce the transmission error and improve the gear carrying capacity. The CAD/CAE integrated modeling and analysis method based on the combination of Matlab， CATIA and finite element commercial software provides methods and tools for the research on tooth surface twist of helical gears with axial modification.